31‐2: Optimization of TFE Structure by FTIR Analysis and Mechanical Simulation to Achieve Excellent Encapsulation and High Flexibility AMOLED. Issue 1 (May 2017) - Chiou, Ji-Yi; Liu, Yen-Wei; Niu, Yi-Fan; Liu, Sheng-Fa; Kuo, Che-Cheng; Hunag, Ching-Yu; Chiu, Yi-Wen; Lai, Ming-Hsiang
Abstract : The 2.7 inch flexible AMOELD is successfully demonstrated through FTIR analysis and mechanical simulation. Through FTIR analysis we can optimize the CVD parameter to realize the SiNx of WVTR 10 −5 (60°/90% R.H.). According to the simulation result, the curvature radius can be reduced to 10mm by modulating the Organic Coating for Planarization(OCP) layer thickness.